KAJIAN TEOLOGIS DI BALIK RITUAL PEMBERSIHAN DAN PENGUDUSAN ISRAEL - Refli, Yohanis; Sarangnga, Citrayanti; Paembonan , Agustina; Juneta , Joice Partiwi; Senga , Yulita Bitta (Relinesia: Jurnal Kajian Agama dan Multikulturalisme Indonesia, 2024)
This study explores the theological underpinnings of cleansing and sanctification rituals in ancient Israelite tradition, highlighting their profound impact on religious and social life. These rituals, which go beyond mere physical cleanliness, symbolise a profound quest for spiritual purity and holiness before God. This study aims to integrate the historical and cultural understanding of these practices from the Old Testament with contemporary Christian theological perspectives. Using a qualitative approach through the literature review method, the research drew from ancient texts such as the Torah and the Gospels, as well as significant theological, historical and cultural works. This approach facilitated a comprehensive exploration of the meaning and implications of the rituals in their original context as well as their reinterpretation in the modern Christian tradition. The research findings emphasise that cleansing and sanctification, in both Jewish and Christian traditions, are intrinsically linked to spiritual transformation a turning from a life of sin to a life dedicated to God. The study also highlights the social and spiritual impact of these practices, emphasising how they strengthen communal bonds and individual spiritual growth. The contemporary relevance of these concepts is clear, providing valuable insights for interfaith dialogue and contributing to the development of a more just and peaceful society. In conclusion, this study confirms the importance of integrating theological understanding in contemporary religious practices, enriching interfaith dialogue and promoting social harmony.